Framing electricity plan choices to enhance green energy usage: A choice experiment with panel data from Germany. (December 2020) - Neumann, Robert; Mehlkop, Guido
Highlights: Renewable energy usage can be enhanced by means of choice architecture. Combining framing with active choices is less paternalistic than altering defaults. Active choices increase the ratio of consumers who opt for green plans. The framing of costs or savings matters for green plan choices. Abstract: This paper investigates the choices and accompanying biases consumers have when actively deciding between two alternative electricity plans. We follow the perspective that observed choices do not necessarily reflect true preferences over outcomes, but are affected by several behavioral tendencies or biases. Our experiment focusses on framing-effects as an important source for such observed behavior. The study is based on data from a large-scale survey experiment conducted in Germany (n = 3320). We implemented a choice experiment in two waves of the GESIS Panel and analyzed more than 16, 000 binary decisions between a standard electricity plan and a supply plan based entirely on renewable energy resources. Across two waves, we manipulated the numerical information as to how the additional costs for buying a green energy plan are presented in the decision problem while keeping the monetary consequences identical between the two waves. We show that framing the consequences of a green electricity plan choice as a foregone saving yields higher rates of green choices than framing the choice of green plan as an additional expenditure. We discuss problems and merits related to the policy strategy of actively framing green energy options that extend beyond the German context.